Functionality of natural killer cells in obese asthma phenotypes - Pur Ozyigit, Leyla; Aktas, Esin Cetin; Gelmez, Yusuf Metin; Ozturk, Ayse Bilge; Gemicioglu, Bilun; Deniz, Gunnur (Clinical and experimental allergy, 2022)
Background Obesity‐associated asthma (OA) is a difficult to treat asthma phenotype due to its severity and poor response to inhaled steroids. Early‐onset allergic (EoOA) and late‐onset non‐allergic (LoOA) OA are suggested subtypes of this phenotype. Natural Killer (NK) cells are key elements of innate immunity involved in cytotoxicity and immune regulation, with uncertain role in OA pathogenesis. Methods Early‐onset allergic and LoOA patients together with obese non‐asthmatic (ONA) controls have been enrolled in the study. Peripheral blood samples have been collected for analysis. Percentages of total NK cells, CD3−CD56dim and CD3−CD56bright NK cell subsets, cytotoxic activity, intracellular interferon‐γ, interleukin (IL)‐10, IL‐13, IL‐17 secretion and activatory receptors (NKG2D, NKp46i and NKp44) have been investigated by flow cytometry. The effect of IL‐12 and IL‐23 stimulation on NK cells and intracellular cytokines in different groups have also been analysed and compared with unstimulated conditions. Results Results of ONA (n = 5, age 42 ± 8), EoOA (n = 5, age 42 ± 10) and LoOA (n = 8, age 46 ± 8) patients have analysed. Body Mass Index has been found to be negatively correlated with CD69 (p = .022, r = −0.534). NKG2D receptor has been significantly low in CD56dim cells of asthma population (p = .046). NKp44 receptor expression has increased after IL‐12 stimulation in EoOA and control group (p = .02). Intracellular IL‐10 content has increased in LoOA and control subjects (p = .018, p = .03) but not in the EoOA group. Intracellular IL‐17 level has found be higher in allergic OA group. LoOA patients showed a decreased NK cytotoxicity compared with the early‐onset asthma group (p = .05). Conclusion Our study suggests an impaired NK receptor expression, activation and reduced cytotoxicity in OA patients together with variances between different subtypes of this phenotype. This data would be beneficial for tailoring a more personalized treatment strategy combatting steroid resistance and frequent exacerbations in this group of patients.